Evaluation of Defense Region Arrangement Policy in Region Space Order Plan of Bandung City, Indonesia - POESPITOHADI, Wibisono; MARSONO, Marsono; KHAERUDIN, Khaerudin (Journal of Advanced Research in Law and Economics; Vol 11 No 2 (2020): JARLE Volume XI Issue 2(48) Spring 2020, 2020)
The 1945 Constitution, article 27 paragraph (3) and article 30 paragraph (1) mandates every citizen about the rights and obligations of every Indonesian citizen in the defense and security efforts of the state. State defense efforts are carried out in a universal defense system involving all citizens. In addition, the arrangement of defense areas throughout the Republic of Indonesia is based on Government Regulation Number 68 of 2014 concerning the Arrangement of National Defense Areas starting from the provincial level to the district/city level. One of them is in the city of Bandung. The implementation of the defense area arrangement is carried out in an integrated manner with the regional spatial plan. But its implementation in the city of Bandung has not been fully integrated. For this reason, research or evaluation of this policy is carried out. The research problem is about the initial conditions (antecedent), the implementation process (transaction), and the achievement results (outcomes) of the defense area arrangement policy in the Bandung City Spatial Plan. The aim of the research is to evaluate the policies at these three stages. This study uses a qualitative method with Stake's Countenance Model. The results of the study show: (1) the initial condition of the defense area arrangement in the Bandung City Spatial Plan has been based on Law Number 26 of 2007 concerning Spatial Planning and has been synergized, but not maximal yet; (2) the policy implementation process has been implemented, but not maximal ye; and (3) the results of the achievement of policies in the form of a Defense Area Plan have been realized and a the Defense Area Detail Plan has not been realized and has not been used as a reference in the preparation of the Bandung City Spatial Plan. The conclusion that the defense area arrangement policy in the Bandung City Spatial Plan was 57.7% in the moderate/moderate category.